Preferred direction of Karst in the Kuala Lumpur Limestone Formation a smart tunnel case study. - Zabidi, Hareyani (Asean Engineering Journal)
In this paper, a karstified limestone formation beneath the city of Kuala Lumpur is studied in reference to its relationship between the geological structure and river patterns. A preliminary prediction of karst that was likely to be readily developed was made based on the existing geological map, where the basic geology of the area was expected to be related to river patterns; which suspected can be obtained from the direction of fractures expected in the limestone. Two directions appear to be special interest : N030 degrees to 070 degrees and N120 degrees to 150 degrees; the investigation was then carried out in the field, using the two sites exposed for construction of the SMART tunnel under Kuala Lumpur to verify the prediction made in the desk study analysis. The method used for this study and the evidence are described.